2007
DOI: 10.1016/j.actamat.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a laser pre-quenched steel substrate surface on the crack driving force in a coating–steel substrate system

Abstract: A mechanical model of a coating/laser pre-quenched steel substrate specimen with a crack oriented perpendicular to the interface between the coating and the hardened layer is developed to quantify the effects of the residual stress and hardness gradient on the crack driving force in terms of the J-integral. It is assumed that the crack tip is in the middle of the hardened layer of the pre-quenched steel substrate. Using a composite double cantilever beam model, analytical solutions can be derived, and these ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…This is because the residual compressive stresses within the substrate always retard the penetration of the vertical coating crack into it, while the residual tensile stresses induce such penetration. Thus, the theoretical prediction by Yang et al (2007) is partly verified, in which it is reported that the as-quenched layer shall retard the penetrating of a vertical crack into the substrate. These results also indicate that a continuous surface quenched layer may induce severe interface fractures when the specimen is subjected to cyclic bending.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…This is because the residual compressive stresses within the substrate always retard the penetration of the vertical coating crack into it, while the residual tensile stresses induce such penetration. Thus, the theoretical prediction by Yang et al (2007) is partly verified, in which it is reported that the as-quenched layer shall retard the penetrating of a vertical crack into the substrate. These results also indicate that a continuous surface quenched layer may induce severe interface fractures when the specimen is subjected to cyclic bending.…”
Section: Resultsmentioning
confidence: 60%
“…In fact, such a residual stress state would lead to great increase in the resistance of the vertical crack extending into the as-quenched regions and increasing the driving force extending into the origin substrate. This has also been argued by Yang et al (2007). Thus, in effect, above the as-quenched regions, the driving force for the vertical crack deflecting into the interface shall be strengthened.…”
Section: Numerical Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Apart from the wear and erosion experiments, it should be emphasized that most of the experiments in the studies mentioned above were restricted to the fatigue property research under dynamic loads. Recently, a mechanical model was developed to quantify the effect of laser quenching on crack driving force in terms of J-integral, and it could be obtained that the dominant factor influencing the crack driving force was the residual stress (Yang et al, 2006(Yang et al, , 2007. However, the residual stress is approximated as a mean value over the crack length, and the residual stress gradient effect was not considered in (Yang et al, 2006(Yang et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8]. Some mechanisms responsible for the improvement have been reported, such as the hardness improvement of the steel substrate surface [8], the finer microstructure of the interface as well as the coating itself [7] and the decrease of the crack driving force in the hardened layer by residual compressive stress and yield strength improvement by the technology [9][10][11]. In this work, a comparative investigation on the initial micro-crack density of the Cr coating on the laser pre-quenched steel substrate surface and original steel substrate surface is investigated.…”
mentioning
confidence: 99%